How do you differentiate -y=lnxy-xyy=lnxyxy?

1 Answer
Jun 27, 2016

y' = - (y - xy^2)/( xy + x - x^2y )

Explanation:

this is a bit easier [administratively] if you use the Implicit Function Theorem...

which says that color{red}{y' = - (f_x)/(f_y)} for function f(x,y) = const

so from
-y=lnxy-xy

we get
y + lnxy-xy \color{blue}{= 0}= f(x,y)

and so....
f_x = 1/(xy)*y - y
= 1/x - y
and
f_y = 1 + 1/(xy)*x - x
= 1 + 1/(y) - x

so using the IFT....
y' = - (f_x)/(f_y)

= - (1/x - y)/( 1 + 1/(y) - x )

= - (y - xy^2)/( xy + x - x^2y )

there are some pretty simple ways to intuit the Implicit Function Theorem

one is to note that if f(x,y) = c

then the total differential df = 0

and df = f_x dx + f_y dy = 0

so dy/dx = - (f_x)/(f_y)